Vocational Guidance : What, Why, How - Mittal, Ritu; Verma, Deepa (Journal of Commerce and Trade, 2008)
The vocational guidance are the backbones for the younger population of any country in general and for the youngsters of a developing country like India is particular as the provide valuable opportunities to get proper ingormation to plan the vocational course for the better tomorrow. The main aim behind vocational guidance is to provide the eduction and training to students which allows them to contribute their best ot the development of the society around them.